Alternatives to the ACA's Affordability Firewall - Nowak, Sarah A. (RAND Corporation, 2015)
The Affordable Care Act implements the employer mandate, which requires firms with more than 50 employees to offer health insurance or face penalties, and the individual "affordability firewall," which limits subsidies to individuals lacking access to alternative sources of coverage that are "affordable." This report examines the policy impacts of the affordability firewall and investigates two potential modifications.